Aldo Sembiring - Sembiring, Aldo frendiko; Winda Evyanto (SCIENTIA JOURNAL, 2022)
Human resources are the most important part in the continuity of an institution or institution. State Elementary School 010 Sagulung is an educational institution in which there are employees who are civil servants or honorary. One of the factors that educational institutions have good quality is the discipline of their employees. There are several factors that affect human resources, which are work supervision, work performance and discipline. The purpose of this research was to assess the impact of work supervision and work discipline together on the performance of teachers at SD Negeri 010 Sagulung Batam. The population in this study were teachers of SD Negeri 010 Sagulung Batam. Total samples in this research were 40 utilize non-probability sampling technique. The data analysis method in this study used multiple linear regression analysis, classical assumption test, statistical test. The results showed, between colleague: (1) work supervision had a positive and meaningful impact on teacher performance; (2) work discipline has a positive and meaningful impact on teacher performance; (3) work supervision and work discipline simultaneously have a positive and meaningful impact on teacher performance.